EFFECT OF POLLARD REPLACEMENT WITH AN RICE BRANIN THE SUPLEMENTATION MINERAL-VITAMIN COMPLEX IN DIETS AGAINST PERFORMANCE OF PIG RAS AGE 2-4 MONTHS - I Km. A., Wijaya; Putri, T. I.; Bidura, I G. N. G. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to determine the effect of pollard replacement with an rice branin the suplementation mineral-vitamin complex in diets against performance of pig ras age 2-4 months. The research was carried out for 2 months in Banjar Lebah Jadi, Jadi Village, Kediri, Tabanan. The design used in the randomized block design (RBD) consisted of 3 treatments, 4 replications. The ration treatment used rations using pollard 18% as a treatment (A), rations using 18% (B) rice bran, rations using rice bran 17.9% + 0.1% complex vitamins (C). Variables observed were feed consumption, final weight, weight gain, and feed conversion ratio. The results obtained will be analyzed by analysis of variance and if there are significant differences (P <0.05) then followed by Duncan's multiple distance test (Steel and Torrie, 1995). The results showed that the consumption of rations with treatment A and treatment B had different consumption not significantly (P> 0.05). In treatment C, ration consumption was 25.66% and 41.78% higher than treatment A and B significantly different (P <0.05). Weight gain in treatment C was 21.78% higher than treatment A but not significantly different (P> 0.05), while treatment C 61.84% was significantly higher than treatment B (P <0.05). FCR in treatment C obtained 14.68% lower than treatment B significantly different (P <0.5). Based on the results of the study it can be concluded that the provision of ration with supplementation of complex minerals as much as 0.10% significantly affected the consumption of rations, final body weight, and FCR in cross-breeds aged 2-4 months.   Keywords: supplementation, boar cross breed, production performance, mineral-vitamin complex